Comparison of Indonesia and Thailand Adoption Regulations: Dialectics of Legal Certainty and Protection of the Best Interests of Children - Br Ginting, Gaby Claryssa; Rahmi, Atikah (Universitas Islam Negeri Alauddin Makassar, 2026)
Adoption is a legal institution that has long-term civil implications for the identity status, family relationships, and rights of children as legal subjects. Differences in adoption regulatory approaches between countries directly impact the level of legal certainty and the quality of child rights protection. This study aims to analyze the comparative legal construction of adoption regulations in Indonesia and Thailand in ensuring legal certainty, as well as to examine the implementation of the principle of the best interests of the child as an effort to protect children's rights. This study uses a qualitative method with a normative-comparative legal approach through an analysis of related laws and regulations, doctrines with Indonesian regulatory laws, such as Law Number 35 of 2014 concerning Child Protection, Government Regulation Number 54 of 2007 concerning the Implementation of Child Adoption, the Compilation of Islamic Law (KHI), and Articles 1598/19–1598/37 of the Thai Criminal Code. The results of the study indicate that Indonesia has built an adoption system within an administrative social protection framework that does not fully guarantee substantive legal certainty, particularly regarding the civil status and inheritance rights of adopted children. In contrast, Thailand has developed a legal assimilation-based adoption model that fully integrates adopted children into the family legal structure, thus providing more comprehensive and long-term legal certainty and protection of children's rights. The application of the child's best interests principle in Thailand has been institutionalized as a substantive legal standard, while in Indonesia it remains declarative-administrative. This study recommends the need for reformulation of legal policies on child adoption in Indonesia to strengthen substantive protection and ensure long-term legal certainty for adopted children.